The guardian - Henderson, Dee (Henderson, Dee. O'Malley series, 2005)
U.S. Marshal Marcus O'Malley tries to protect a beautiful woman from the unknown killers who want her dead because she has witnessed a murder. The woman, a speechwriter named Shari, is a Christian. As romance blooms between Marcus and Shari, he begins to rethink the faith that he lost when his mother died.